Exploring Job Preferences among Final-Year Undergraduate Public Health Students in Indonesia - Dian Mawarni; Nurhasmadiar Nandini; Anindya Hapsari; Tika Dwi Tama; Mika Vernicia Humairo (Preventia : The Indonesian Journal of Public Health, 2025)
Although the number of public health graduates has rapidly increased, public health workforce scarcity remains challenging in Indonesia. Understanding job preferences among students majoring in health is essential for health workers in the future. The purpose of this study is to investigate undergraduate public health students’ stated preferences when choosing a workplace and occupations after graduation and to explore factors that are related to choices of employment. An online survey was carried out in June 2023. Respondents were asked questions that collected sociodemographic and academic characteristics and information related to their preferred workplace and occupation. Descriptive statistics were measured using frequencies and proportions, and analytic statistics were performed using the Chi-Square test. An alpha level of 0.05 was employed to determine significance. A total of 275 undergraduate public health students completed the questionnaire. Over fifty percent preferred government health agency as workplaces and public health professionals as occupations. Significant factors related to job preferences were categorized into individual characteristics and academic background. These findings predict the public health workforce shortages due to public health graduates experiencing difficulties finding jobs and entering work in government settings, so some decide to work outside the government.